Social Justice as the Goal of Development Law in the 2025-2029 National Medium-Term Development Plan - Cassis Merinthia Ariapramuda; Irena Puspa Mega; Nur Rizkiah Hasanah; Atiek Pratiwi Putri Naue; Diani Sadiawati (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Social justice constitutes a fundamental principle embedded in the Fifth Precept of Pancasila and the Preamble to the 1945 Constitution of the Republic of Indonesia, positioning it as both a legal ideal and a guiding orientation for national development. This study examines the conceptual position of social justice as the objective of Indonesia's development law and evaluates the extent to which this principle is reflected in the National Medium-Term Development Plan (RPJMN) 20252029. Employing a normative juridical method with conceptual and statutory approaches, this research analyzes the integration of social-justice values into development policies articulated in the RPJMN. The findings reveal that, conceptually, social justice is affirmed as a central objective of Indonesia's development law, consistent with Mochtar Kusumaatmadja's Development Law Theory. The RPJMN 20252029 demonstrates partial incorporation of social-justice principles through its eight national priorities, particularly those emphasizing equitable development outcomes, the eradication of extreme poverty, and the development of distributive infrastructure. Nonetheless, key challenges remain in regulatory harmonization and evaluation mechanisms, which have not fully employed social-justice benchmarks. This study contributes to the existing scholarship by proposing the adoption of a social justice impact assessment as a mandatory component in development planning documents and advocating for strengthened inter-institutional coordination in implementing distributive justice-oriented development policies.